The interplay between steric repulsions and metal-metal bonding in [Ru-2(mu-Cl)(3)(PR3)(6)](z+), R = H, Me, Et, z = 1, 2, 3: a hybrid QM/MM study - Knottenbelt, S; McGrady, J; Heath, G (2003)
The hybrid quantum/molecular mechanics methodology is used to examine the interplay between metal-metal bonding and steric effects in a series of isostructural redox-related ruthenium dimers. Potential energy surfaces for the various electronic states arising from (d6d6) (1 +), (d5d6) (2+) and (d5d5) (3+) configurations are explored. Somewhat counterintuitively, the bulky groups on the phosphine ligands are found to have most effect when the Ru-Ru bonding is strongest. The origin of this trend has been traced to the nature of the steric interactions, which are largely between the bridging halides and the substituents on the phosphine. As the Ru-Ru bond contracts, a concertina-like motion displaces the halides away from the trigonal axis and towards the phosphine substituents. The resulting competition between Ru-Ru bonding and steric repulsions means that varying the bulk of the phosphine provides an efficient mechanism for tuning or even completely eliminating the metal-metal bond. © The Royal Society of Chemistry 2003.